1997
DOI: 10.1046/j.1365-2133.1997.19882069.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha hydroxyacids modulate stratum corneum barrier function

Abstract: Alpha hydroxyacids (AHAs) are used to enhance stratum corneum desquamation and improve skin appearance. The purpose of this study was to evaluate whether some AHAs improve skin barrier function and prevent skin irritation. Eleven healthy subjects (aged 28 +/- 6 years, mean +/- SD) entered the study. Six test sites of 8 x 5 cm (four different AHAs, vehicle only (VE) and untreated control (UNT) were selected and randomly rotated on the volar arm and forearm. The four different AHAs at 8% concentration in base cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 5 publications
1
66
1
1
Order By: Relevance
“…In previous studies, we demonstrated that transient perturbations in SC pH, induced by topical applications of either superbases (Hachem et al, 2003) or polyhydoxyl acids (Berardesca et al, 1997), do not alter basal permeability barrier function, as assessed by transepidermal water loss (TEWL) (see also Ritter et al, 2001). Moreover, prior studies have shown that treatment with agents such as 1,1,3,3-tetramethylguanidine (TMG) (a superbase) also does not produce cell toxicity, as assessed by light or electron microscopy (Berardesca et al, 1997;Hachem et al, 2003). To determine whether SC acidification/ neutralization regulates NHE1 expression independent of barrier status, either TMG (a superbase) or lactobionic acid (LBA) (a polyhydroxyl acid) was applied to the flanks of Acidity at the skin surface decreases after barrier disruption.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In previous studies, we demonstrated that transient perturbations in SC pH, induced by topical applications of either superbases (Hachem et al, 2003) or polyhydoxyl acids (Berardesca et al, 1997), do not alter basal permeability barrier function, as assessed by transepidermal water loss (TEWL) (see also Ritter et al, 2001). Moreover, prior studies have shown that treatment with agents such as 1,1,3,3-tetramethylguanidine (TMG) (a superbase) also does not produce cell toxicity, as assessed by light or electron microscopy (Berardesca et al, 1997;Hachem et al, 2003). To determine whether SC acidification/ neutralization regulates NHE1 expression independent of barrier status, either TMG (a superbase) or lactobionic acid (LBA) (a polyhydroxyl acid) was applied to the flanks of Acidity at the skin surface decreases after barrier disruption.…”
Section: Resultsmentioning
confidence: 96%
“…In prior studies, a-hydroxy-acids, such as gluconolactone (GL), another polyhydroxyl acid, were shown to accelerate permeability barrier recovery and prevent skin irritation (Berardesca et al, 1997). This effect was not equal among all ahydroxy-acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased percutaneous penetration can result. In contrast, hyperacidification of the stratum corneum in hairless mice using lactobionic acid (LBA) and gluconolactone (GL) can enhance permeability barrier homeostasis and stratum corneum desquamation (32). Drugs usually exist in unionized or ionized forms depending on their pKa (drug dissociation constant) relative to skin pH.…”
Section: Age-related Percutaneous Penetrationmentioning
confidence: 99%